Navigating the path to care and death at home—it is not always smooth: a qualitative examination of the experiences of bereaved family caregivers in palliative care. Issue 1 (July 2019) - Lobb, Elizabeth A.; Bindley, Kristin; Sanderson, Christine; MacLeod, Roderick; Mowll, Jane
Abstract: Background: Care and death at home are generally thought to be beneficial for families. However, there may be bereavement experiences and support needs, which are specific to family caregivers providing end-of-life care in their home. The Palliative Care Home Support Program in New South Wales, Australia, provides end-of-life care packages for patients who wish to die at home. These packages provide up to 48 hours of specialized supportive palliative home-based care, day or night, by community workers specifically trained for the task, working as part of existing community palliative care multidisciplinary teams. Care packages may include assistance with personal hygiene, carer respite, and domestic assistance. Methods: As part of a larger longitudinal mixed-methods study, 28 bereaved caregivers who experienced a home death and/or received the care packages undertook in-depth interviews. Narrative thematic analysis was undertaken to explore their experiences at 6 months post death. Results: Twenty-eight caregivers were experienced or planned for a home death and 21 had a package in place. Five themes were identified: "the achievements of a home death"; "taking on the mantle"; "the burden of witnessing the dying process"; "home as our space/their space"; and "resistance or submission to the ideals of best place of care for family caregivers." Conclusions: Bereaved caregivers provided accounts of their interactions with health care providers depicting a complex relationship with the care system. Some families struggled to manage boundaries of home and private space as care needs escalated. Ideals about best care and home death are sometimes conflicted, without easy consensus between patient, family, and service providers. Significance: Models of care based on assumptions that home death is straightforwardly beneficial may cause unintended consequences. For future policy, providing care in the private space of the home requires close attention to family concerns and outcomes.